Aggression Depicted in Suzanne Collins’ The Hunger Games - NANING CHOIRUN NISA (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2014)
Aggression Depicted in Suzanne Collins’ The Hunger Games NaningChoirunNisa English Department, Faculty of Languages and Arts, State University of Surabaya Naningc5@gmail.com Prof. Dr. FD Kurnia, M.Pd. English Department, Faculty of Languages and Arts, State University of Surabaya Abstrak Studiinimembahastentangagresi yang dilakukanolehparapesertaThe Hunger Games, merekaadalahKatniss, Peeta, Cato, Clove, Glimmer, dan Thresh. Agresitelahmenjaditopikutamadidalam novel yang diterbitkantahun 2008 ini.Olehkarenaitu, studiinimembahasduapermasalahan, yakni (1) bagaimanaagresidigambarkan di The Hunger Gameskarya Suzanne Collins, dan (2) mengapaagresiterjadisebagaimanasepertiyang digambarkan di The Hunger Games karyaSuzanne Collins. Data daristudiinidiambildari novel sebagaisumberutamadanjugamembacasecaraintensifsebagailangkahselanjutnyauntukanalisis.Studiinimenggunakankonsepagresidaribeberapaahlidankonsepdeath instinctdari Sigmund Freud.Untukmenyelesaikanrumusanmasalahpertama, studiinimenggunakankonsepagresiuntukmendiskripsikanbagaimanaagresidilakukanolehparapeserta di dalamThe Hunger Games.Kemudianrumusanmasalahkeduadiselesaikanmenggunakanpendekatanpsikologiyakniteorideath instinctdanjugakonsepagresidari Anderson & Bushman untukmengungkapkanfaktorsituasidibaliktindakanagresiparapeserta.Terlebihlagi, penulismenggunakanpendekatanperpustakaan, analisis, danpenggambaran.Pendekatanperpustakaandigunakanuntukmencari datayang kemudiandianalisisberdasarkanteori yang ada.Penggambarandigunakanuntukmenjelaskanhasildarianalisis.Setelahmelaluianalisis yang panjangdenganmenggunakantigametodetersebut, makadapatdigambarkandenganjelasagresi yang dilakukanolehparapeserta, yakniKatniss, Clove, Cato, Peeta, Glimmer, dan Thresh.Hampirsemuatindakanagresimerekadipengaruhiolehdeath instinct, tindakanyang mengarahkepembinasahan, dantindakanagresikarenafaktorsituasi, sepertiisyaratagresi, provokasi, frustrasi, perasaansakitdantidaknyaman, obat-obatan, sertadorongan. Kata kunci :Agresi; kekerasan; death instinct; danfaktorsituasi. Abstract This paper deals with aggression done by the tributes of the hunger games, they are Katniss, Peeta, Cato, Clove, Glimmer, and Thresh. Aggression has become the main topic of this novel since it was published in 2008. Thus this study focuses on two major problems, (1) how is aggression depicted in Suzanne Collins’ The Hunger Games, and (2) why is aggression happened as depicted in Suzanne Collins’ The Hunger Games. The data of the thesis is taken from the novel as the main source and intensive reading to next step of analysis. The concept that will be used includes the concept of aggression by several experts and death instinct by Sigmund Freud. To answer the first problem, this study is using the concept of aggression to depict the aggression that is done by the tributes in the hunger games. Then the second problem is answered by using psychological approach of death instinct theory and the concept of aggression by Anderson & Bushman to reveal the situational factors behind their aggressions. Moreover, the writer used library research, analysis and description. Library research is used to college data needed. An analysis is used to analyze the collected data based on the theories. Description is used to describe the result of analysis. After getting through long analysis by using three kinds of method above, it can reveal the depiction of aggression that is done by the tributes, Katniss, Clove, Cato, Peeta, Glimmer, and Thresh and most of their factors to do aggression is following their death instinct to destruction and aggression because of the situational factors, such as aggressive cues, provocation, frustration, pain and discomfort, drugs, and incentives. Keywords: aggression; violence; death instinct; and situational factors. INTRODUCTION: One of the main concern that has been increased nowadays is the issue of violence. Violence must be close related with aggression. As the World Health Organisation (1996) defines violence as an action that used the intentional of physical power, threatened or actual, against oneself, another person, or against a group or comunity that has results of harm. Anderson et al. (2002:29) state that violence is aggression whose goal is serious and extreme harm, i.e. death. All violence can be defined as aggression. However aggression is not always violent,i.e., a dentist intentionally gives a patient a shot of Novocain (it might be hurt), but the goal is to help rather than hurt the patient. In social psychology, the term of aggression is generally defined as any behavior that is intended to harm others who does not want to be harmed. Aggression is an external behavior that can be seen. i.e., a person shoots, hits, slaps, or threats someone. Aggression is a social behavior. It involves at least two people. In addition, aggression is intended to hurt, it is not happened accidental. Hence, an extreme and serious aggression may lead to violence. Aggression on violence has been a serious problem over the past decades. It can take several forms; physical aggression, verbal aggression, and relational aggression. Moeller (2001:25) defines physical aggression as actual physical activities that is intentionally intended to harm another person, animal, or object. i.e., hitting, pinching, hair-pulling, arm-twisting, strangling, burning, stabbing, punching, pushing, slapping, beating, shoving, kicking, choking, biting, force-feeding, threats with a weapon or object, any other rough treatment, or even murder.Verbal aggression involves the use of words to harm another persons,i.e.,teasing andthreatening (Moeller, 2001:25). Crick et al. cited in Moeller (2001:25) define relational aggression as “behaviors that harm others through damage (or the threat of damage) to relationships or feelings of acceptance, friendship, or group inclusion”. Whereas relational aggression, Crick &Grotpeter (1995) state that it is a behavior that is intended to hurt someone by harming their relationships with others. Furthermore, aggression on violence has portrayed in literature, i.e., in the novel. Novel deals imaginatively with human experience. Novel is a genre of fiction, and fiction may be defined as the art through the written word, representations of human life that instruct or divert or both(http://global.britannica.com/EBchecked/topic/421071/novel). One of the American author deals with the theme of aggression and violence in its works is Suzanne Collins. She is the author of several novels for younger readers. Collins, a 48-year-old mother of two children, began her writing career in television. Collins spent the 1990s writing kids’ shows for Nickelodeon, including Clarissa Explains It All (1993) and The Mystery Files of Shelby Woo (1997-98). She has also written for pre-school viewers on programs like Little Bear (1995-2003) and Oswald (2001-2008). Few other famous works of Collins includes her book Fire Proof: Shelby Woo (1999). When Charlie McButton Lost Power (2005) and When Charlie McButton Gained Power (2009). Then Collins switched to writing novels for young readers, and between 2003 until 2007 published five novels in The Underland Chronicles series: Gregor the Overlander (2003); Gregor and the Prophecy of Bane (2004); Gregor and the Curse of the Warmbloods (2005); Gregor and the Marks of Secret (2006); and Gregor and the Code of Claw (2007). In the same way, between 2008 until 2010 she published the other Series under the name The Hunger Games trilogy. These three books were The Hunger Games (2008); Catching Fire (2009); and Mockingjay (2010). Overall the series of The Hunger Games has been a great success, they are sold in more than 50 million print and electronic copies. The Hunger Games book has made a film version released in 2012 and for the second book Catching Fire in 2013. In addition, TheHunger Games novels have made Collins extremely popular amongst readers, and led her to be named one of Time Magazine’s Top 100 people in 2010, The New York Times Bestseller, 2009-10; Publishers Weekly Best Book of the Year, 2008; American Library Association (ALA) Best Book for Young Adults, 2009; and others. The Hunger Games has spent more than 260 consecutive weeks or more than five consecutive years to date on The New York Times bestseller list since publication in September 2008, and has also appeared consistently on USA Today and Publishers Weekly bestseller lists. It has been sold into 56 territories in 51 languages. However, some critics still appreciate the novel. “I was so obsessed with this book … The Hunger Games is amazing.” — Stephanie Meyer. (http://www.thehungergames.co.uk/press_and_reviews) Hence this paper will discuss aggression in the hunger games based on Suzanne Collins’ first trilogy The Hunger Games where she reveals an outsize imagination for suffering and brutality in the post-apocalyptic nation of Panem, formerly known as North America. In Panem, the hunger games are an annual game which one boy and one girl between the ages of 12 to 18 years from their respective districts around the Capitol compete in a deadly battle until only one winner remaining. The winner will be famous and given prosperous life. The Hunger Games much presents on aggression that leads to violence. As Dewall et al. (2011:2) argue that violence is any aggressive behavior which is aimed to make harm physicaly, such as injury or death. Hence, theory of death instinct (thanatos) by Sigmund Freud and concept of aggression by Anderson & Bushman have developed to explain the reason of the tributes (Katniss, Peeta, Cato, Clove, Glimmer, and Thresh) doing aggression and violence acts. Thus, this study will discuss deeper aboutwhy people develop behaviors intended to hurt others as seen in The Hunger Games. Theoritical Framework Toassistandstrengthenthe datatobe analyzed, it willusea concept of aggression by several experts. To analyze the reasons that influence aggression, it will be explained frompsychological perspective (death instinct) by Sigmund Freud adds with concept of aggression by Anderson & Bushman. Based on the background of the study above, the questions below will be answered. How is aggression depicted in Suzanne Collins’ The Hunger Games? Why does aggression happen as depicted in Suzanne Collins’ The Hunger Games? Data Collection The data collection is taken from the novel The Hunger Games including the quotations, phrases, dialogues, or monologues in which reveal thought, speech, action, and attitude that reflects the idea of aggression. Limitation of the Study This study is limited and focused on aggression as depictedin Suzanne Collins’ The Hunger Games.The subject of this aggression is the tributes of The Hunger Games. They are KatnissEverdeen, Peeta, Cato, Clove, Glimmer, and Thresh. Thus, the focus on this study is the tributes of the hunger games who have done much aggression to hurt and harm others. The actions of the tributes of The Hunger Games in form of quotations, phrase, dialogues, or monologues in the novel that reveal as aggression, are taken as the data. Procedure of Analysis There were some steps taken in conducting this study. The first step is close reading of the novel to determine the major issue of it. The major issues are collected and proposed into a topic of the study by seeing the conflict, the monologue, the dialogue in the novel. After the topic is already decided, it is tried to figure out what should be analyzed with the topic. Thus it is collected two statements of problems. They are the depiction of aggressionand the factors that influence aggression in The Hunger Games. The next step is searching related information about concept of the topic and to figure it out, it is used a concept of aggression and a theory of death instinct (thanatos) by Sigmund Freud adding with concept of aggression by Anderson & Bushman. The synchronization of analysis and related concept was arranged to get the conclusion. RESULT Concept of Aggression In essence, aggression is an action that harms person or object (Moeller, 2001:2). Bartol cited in Moeller (2001:24) defines aggression as behaviors intended intentionally to harm another person physically or psychologically or to destroy or to take that person’s property. In additional, The Collins Concise Dictionary also defines aggression as “an attack, a harmful action, an offensive activity, a hostile, or destructive mental attitude.” (Harding, 2006:3). Aggression can start from the “low-level” acts, such as being impolite, making minor threats, and violating minor rules that are generally annoying acts. (Moeller 2001:22) Bartol et al. cited in Moeller (2001:25) state that aggression can also be hostile, instrumental, or reactive. Hostilehas the main purpose to harm or suffer the victim.Hostile aggression is driven byarousal, impulsivity, and immediate to situationalprovocation. It may be closer to the kinds of aggressionidentified by instinct theories. It includes irritableaggression.Instrumental aggression refers to unprovoked aggression used more force to get nonaggressive actions from the victim. Instrumental aggression is a learned response where aggression is a mechanism forachieving certain goals.In this mode aggression is just another way of gettingwhat you want or avoiding being criticised by authorityor gaining normal awards. i.e., a child beats another child to take some money (Bartol et al. cited in Moeller, 2001:25). In essence, instrumental aggression is not commonly followed by emotional feeling. It is just used as a way to get something else. Instrumental aggression involves defensive action, fight to get authority or want to dominate others.Whereas reactive aggression called as provoked aggression. It refers to an angry acts in response to some provokating environmental event or behaviors (Bartol et al. cited in Moeller, 2001:25). According to Pawlik et al. (2000:195) state that aggression that is used to survive depends on the individual organisms securing environmental resources. i.e., water as resources is freely available in humid country, so it does not need to fight to get it. The predatory species always hunt to get the food, on the contrary the prey (food) may resist themselves. Both predators and prey may engage in aggressive attack and defensive actions in this case. Furthermore, in his term of “intra-specific interactions”, Pawlik et al. explain that as individuals of the same species often have to compete for resources such as food or shelter. In one hand, in intra-specific antagonism aggression may occur in competition for social resources, i.e., mating partners or alienating. Characteristics of Aggression From some explanation of aggression above can be concluded the characteristics of aggression are: Aggression is aimed to hurt, to harm or to destroy others. Aggression is a release action of frustration, anger, or bad feeling. Types of Aggression Physical aggression Moeller (2001:25) defines phisical aggression as actual phisical activities that is intentionally intended to harm another person, animal, or object. i.e., hitting, pinching, hair-pulling, arm-twisting, strangling, burning, stabbing, punching, pushing, slapping, beating, shoving, kicking, choking, biting, force-feeding, threats with a weapon or object, any other rough treatment, or even murder. Verbal aggression Verbal aggression involves the use of words to harm another persons for such as teasing andthreatening. (Moeller, 2001:25) Verbal aggression includes acts such as insulting with bad language, displaying anger, threatening, swearing and being sarcastic all in order to cause emotional and psychological pain (Sameer &Jamia 2007), while National Youth Violence Prevention Research Centre (2002) state that verbal aggression includes such behaviors as threatening, intimidating others and engaging in malicious teasing and name-calling. (Onukwufor, J., 2013:64) Teasing is one of the type of verbal aggression. Teasing can be “playful” or “hurtful”. According to Dess, J. et al. (2011:2) state that teasing can be “playful” when; (1) teasing is used when we are talking with friends and everyone involves in the teasing, it is called as ‘teasing pie’, (2) teasing isn’t aimed to hurt, (3) teasing is done by closed friends, and (4) teasing is repeated again. However, teasing can be “hurtful” when; (1) teasing tends to direct into one person in a group, (2) teasing is sometimes repeated, (3) teasing is done by someone whom we do not recognize, (4) it is used to make fun of someone who having disability. Relational aggression Crick et al. cited in Moeller (2001:25) define relational aggression as “behaviors that harm others through damage (or the threat of damage) to relationships or feelings of acceptance, friendship, or group inclusion.” Crick &Grotpeter (1995) also agree that relational aggression is behavior that is intended to hurt someone by harming their relationships with others.(http://www.hopehouseonline.org/pages/gorls.shtml, 2010-2011) Little, Jones, Henrich, & Hawley cited in Young E. (2010:2) categorize relational aggression into two parts; reactive relational aggression and instrumental relational aggression. Reactive relational aggression is used to respond to provocation. People used this aggression by manipulating social issues, such as spreading rumors, as a response to feeling threatened or angry. Whereas instrumental relational aggression is “manipulating relationships or using aggression to get what one wants.” The Relationship between Aggression and Violence Anderson, C., &Huesmann, L. cited in Hogg & Cooper (2003:298) state that aggression is any behavior that is intended to harm directed toward others. Furthermore the agent of aggression will make sure that his aggression will harm the target. However, the target will automatically avoid the aggression as a defensive action. Anderson, C.A., & Bushman B.J. (2002:29) state that violence is aggression that has extreme harm as its goal, i.e., death. Tolan and Guerra cited in Moller (2001:2) state that violence is “the most extreme and serious” form of aggression. Anderson et al. (2002:29) state that all violence can be defined as aggression. However, in some cases of aggression are not always violent. i.e., a child is pushing his friend’s tricycle is an act of aggression but is not an act of violence. To reach that serious and extreme goal, such as injury or even death, must be expressed into visible way, i.e., physical aggression. Thus aggression can lead to violence if it is happened on physical aggression. Because the goal of aggression that leads to violence is to hurt and to harm the target of aggression. Moreover, Anderson, C., &Huesmann, L. cited in Hogg & Cooper (2003:298) also agree that “violence is physical aggression at the extremely high end of the aggression continuum, such as murder and aggravated assault.” Harding (2006:4) adds that aggression is the easiest to recognize in violence. She calls it as “the rawest manifestation being ‘destructive motor action’.” In addition, The World Health Organisation (1996) also defines violence as an action that used the intentional of physical power, threatened or actual, against oneself, another person, or against a group or comunity that has results of harm or even death. Hence, in social psychology, violence is aggression that has extreme physical harm as its goal, such as injury or death. One child intentionally pushing another child down is an act of aggression but it is not an act of violence. One person intentionally hitting, kicking, shooting, or stabbing another person is an act of violence. Thus, violence is a subset of aggression. All violent acts are aggressive, but not all aggressive acts are violent (only the ones that are intended to cause extreme physical damage are called violent). Factors Influencing Aggression Drives Drive derived from a German word Trieb which refers to a stimulus within person. This word is generally understood as instinct, inborn patterns of behavior that are biologically determined rather than learned with its characteristics that are both physical (bodily needs) and psychological (wishes). Drives operate as a constant motivational force. Freud proposed that drives consists of two parts; sex (eros) and aggression (thanatos). (Feist, 2008:31) Death Instinct Death Instinct is the concept made by a psychoanalist, Sigmund Freud. Thomas cited in Moeller (2001:26) states that Freud assumes that human born with a drive, called the Thanatos. To Allen (2006:24), thanatos is the instinct toward destructiveness and death which is aimed at returning living things to their original lifeless state. Freud stated in Li (2011:116) defines thanatos as “an urge inherent in organic life to restore an earlier state of things”. Thanatos might be directed toward the self that is resulting in self-injury or even death, it can be also directed toward others that is resulting in aggression. The instinct theory of aggression derives mainly from two sources: psychoanalysis and ethology. According to psychoanalytic theory, human behavior is motivated by two sets of opposing instincts: Eros, consisting of all those forces aimed at furthering life, and Thanatos, consisting of all those forces striving for the destruction of life (Freud, 1933). When Thanatos, the death instinct, is discharged outward, the result is aggressive behavior. If this instinctual drive is not expressed, it continues to build up within the individual until it is relieved either by an explosive act of violence or until it is turned inward as self-destructive behavior. Since the aggressive drive is constantly seeking an outlet, the theory is basically a pessimistic one in that aggression is seen as an unavoidable part of human behavior. Indeed, Montague (1968) has argued that instinct theory, in its emphasis on the hostile and destructive nature of humans, relates quite closely to the doctrine of the